Bean seeds: leading nutraceutical source for human health. Issue 1 (2nd January 2016) - Suárez-Martínez, Silvia Esperanza; Ferriz-Martínez, Roberto Augusto; Campos-Vega, Rocio; Elton-Puente, Juana Elizabeth; de la Torre Carbot, Karina; García-Gasca, Teresa
Abstract : Phaseolus is the most important food legume for human consumption in the world. Its seeds consist mainly of carbohydrates and are a good source of nitrogen and protein. It also contains calcium, magnesium, potassium, phosphorus, copper, iron, zinc, manganese and sulfur. This legume is rich in bioactive components such as enzyme inhibitors, lectins, phytates, oligosaccharides and phenolics, which exhibit metabolic roles in humans and animals. Among the observed biological activities are the antioxidant capacity, the reduction of cholesterol and reduction of low-density lipoproteins, thus Phaseolus has a protective effect against cardiovascular diseases. Also it has shown favourable effects against cancer because of the antimutagenic and antiproliferative properties of their phenolics, lectins and protease inhibitors. Additionally, it has showed effects on obesity and diabetes due to its content of resistant starch and α-amylase inhibitor. Here we present a review of the beneficial properties of beans as a nutraceutical food.